2019
DOI: 10.18483/ijsci.1853
|View full text |Cite
|
Sign up to set email alerts
|

Early Event Detection and Discontinuation of the Culprit Drug Increases the Rate of Survival in Severe Cutaneous Adverse Drug Reactions: A Multi-Center Study in Bangladesh

Abstract: Adverse drug reactions are completely unwanted drug reactions derived from self-medications and among those unpleasant reactions, severe cutaneous adverse drug reactions like, Stevens-Johnson Syndrome, Toxic Epidermal Necrolysis, Acute Generalized Exanthematous Pustolosis and Drug Reaction with Eosinophilia and Systemic Symptoms, are mostly life threatening harms, globally. The main objective of this study was to find out the impact of early detection of the adverse drug events and consequently prompt withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In almost all the papers, ABs were one of the major causes of cADRs or ScADRs. The lowest frequency was found to be between 5% -10% [15,26,42] and highest being 81.13% [70] followed by 73.8% [71]. Several other studies also found a very high frequency of AB-associated cADRs like- Wong et al, (2019) [72] 66.1%, Dimri, Raina, Thapliyal, & Thawani, (2016) >69% [11], and Verma et al, 56% [73] (Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…In almost all the papers, ABs were one of the major causes of cADRs or ScADRs. The lowest frequency was found to be between 5% -10% [15,26,42] and highest being 81.13% [70] followed by 73.8% [71]. Several other studies also found a very high frequency of AB-associated cADRs like- Wong et al, (2019) [72] 66.1%, Dimri, Raina, Thapliyal, & Thawani, (2016) >69% [11], and Verma et al, 56% [73] (Table 2).…”
Section: Discussionmentioning
confidence: 87%
“…In almost all the papers, ABs were one of the major causes of cADRs or ScADRs. The lowest frequency was found to be between 5% -10% [15,26,42] and highest being 81.13% [70] followed by 73.8% [71]. Several other studies also found a very high frequency of AB-associated cADRs like- Wong et al, (2019) [72] 66.1%, Dimri, Raina, Thapliyal, & Thawani, (2016) >69% [11], and Verma et al, 56% [73] (Table 2).…”
Section: Discussionmentioning
confidence: 87%